Reformasi Kebijakan Keimigrasian di Era Globalisasi: Studi Komparatif Indonesia dan Negara ASEAN Lainnya - Agid Lukas Evans Pardede; Aninda Sri Rahayu Mastur; Rahmawati Nurul Jannah (Universitas 17 Agustus 1945 Semarang, Indonesia, 2025)
This study analyzes Indonesia’s immigration policy reforms in response to global and ASEAN migration dynamics. The reforms emphasize a human rights-based approach, digital services like e-Visa and M-Paspor, and bureaucratic modernization. Despite progress, challenges remain in implementation, institutional overlap, and limited protection for vulnerable groups such as refugees and undocumented migrants. Comparisons with other ASEAN countries reveal varied approaches, positioning Indonesia to lead regional migration policy harmonization through its strategic role and commitment to human right.